Electrical Stimulation Therapy – Dedicated to the Perfect Plastic Repair - Kexin Deng; Ruizeng Luo; Ying Chen; Xiaoqiang Liu; Yuanyin Xi; Muhammad Usman; Xupin Jiang; Zhou Li; Jiaping Zhang (Advanced Science)
Abstract Tissue repair and reconstruction are a clinical difficulty. Bioelectricity has been identified as a critical factor in supporting tissue and cell viability during the repair process, presenting substantial potential for clinical application. This review delves into various sources of electrical stimulation and identifies appropriate electrode materials for clinical use. It also highlights the biological mechanisms of electrical stimulation at both the subcellular and cellular levels, elucidating how these interactions facilitate the repair and regeneration processes across different organs. Moreover, specific electrode materials and stimulation sources are outlined, detailing their impact on cellular activity. The future development trends are projected from two perspectives: the optimization of equipment performance and the fulfillment of clinical demands, focusing on the feasibility, safety, and cost‐effectiveness of technologies.